Andragogy characteristics of undergraduate students' towards web-based technology of learning in association to teaching strategies / Salina Budin, Aznifa Mahyam Zaharudin and Shaira Ismail - Budin, Salina; Zaharudin, Aznifa Mahyam (Penerbit UiTM (UiTM Press), 2015)
An increasing number of undergraduate students' enrolment and high capability of technology advancement contribute to an enormous change in the teaching and learning perspectives. It has led to an evolution in the educational field. Traditional teaching strategies are no longer favourable and have been traded with web-based technology teaching strategies. This new style of teaching strategy demands a high level of students' responsibilities' to be more independent and highly self-directed and motivated towards their own learning. In other words, they must be andragogy oriented. This study attempted to investigate the readiness level among undergraduate students towards web-based technology learning. The main purpose of this work is to identify whether undergraduate students who are categorized as young adults are andragogy oriented individuals.